Answer:
it is an example of an expression
Step-by-step explanation:
it is an example of an expression because it is asking a question without an equal sign. so its not a question, but an expression
Answer:
A (4-g)1.5
Step-by-step explanation:
hope this helps if you need a explanation just ask in the comments and I will.
Answer:
240
Step-by-step explanation:
Hello from MrBillDoesMath!
Answer:
x = 1/2 (1 +\- i sqrt(23))
Discussion:
x \3x - 2 = (x/3)*x - 2 = (x^2)/3 - 2 (*)
1 \3x - 4 = (1/3)x - 4 (**)
(*) = (**) =>
(x^2)/3 -2 = (1/3)x - 4 => multiply both sides by 3
x^2 - 6 = x - 12 => subtract x from both sides
x^2 -x -6 = -12 => add 12 to both sides
x^2-x +6 = 0
Using the quadratic formula gives:
x = 1/2 (1 +\- i sqrt(23))
Thank you,
MrB